1995
DOI: 10.1212/wnl.45.12.2154
|View full text |Cite
|
Sign up to set email alerts
|

Verbal memory impairment resulting from hippocampal neuron loss among epileptic patients with structural lesions

Abstract: We recently demonstrated statistically significant correlations between presurgical memory impairment and hippocampal volumetric cell densities (in CA3 and the hilar area only) for patients with idiopathic left temporal lobe epilepsy who exhibited marked hippocampal neuron loss. In the present research we determine whether the same relationship exists for patients with structural lesions, in whom hippocampal neuron loss was minimal. Rank-order correlations of verbal memory test results (ie, Long Term Retrieval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 2 publications
7
29
0
Order By: Relevance
“…In the literature, left HS was correlated with deficiency of verbal, right HS with impairment of visuo-spatial memory, and the severity of memory deficits was related to the degree of HS detected with MRI or 1 H MRS [41][42][43]. In addition, the degree of pyramidal cell loss in Ammon's horn and loss of hilar neurons and granule cells of the dentate gyrus correlated to memory impairments [44,45,[47][48][49]. In the present study, we show that not only neuronal loss but also a more subtle, morphological and neurochemical alteration, namely decreased CB expression in the granule cells of the dentate gyrus, is associated with a deficit in memory functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, left HS was correlated with deficiency of verbal, right HS with impairment of visuo-spatial memory, and the severity of memory deficits was related to the degree of HS detected with MRI or 1 H MRS [41][42][43]. In addition, the degree of pyramidal cell loss in Ammon's horn and loss of hilar neurons and granule cells of the dentate gyrus correlated to memory impairments [44,45,[47][48][49]. In the present study, we show that not only neuronal loss but also a more subtle, morphological and neurochemical alteration, namely decreased CB expression in the granule cells of the dentate gyrus, is associated with a deficit in memory functions.…”
Section: Discussionmentioning
confidence: 99%
“…The severe neuronal loss, typical for HS, may also be responsible for memory impairments, as shown earlier [44][45][46][47][48][49]. Therefore, patients were separated into two groups by the etiology and MRI findings.…”
Section: Correlation Between Cb Immunoreactivity and Patients' Neuropmentioning
confidence: 99%
See 1 more Smart Citation
“…Following resection of their epileptogenic temporal lobes, cell densities in different areas of the hippocampus were determined and correlated with cognitive performances. Scores on verbal memory tests were found to correlate with the cell density in the left hippocampal areas CA1 [Rausch and Babb, 1993;Sass et al, 1995], CA2 [Sass et al, 1995] as well as CA3 and the hilar region [Sass et al, , 1990. These findings were further demonstrated to be specific to mnestic function since correlations could not be found between neurone densities and tests of confrontation naming or IQ [Rausch and Babb, 1993;Sass et al, 1992].…”
Section: Introductionmentioning
confidence: 89%
“…On a biological level, memory impairments of this kind have been found to be attributable to hippocampal damage specifically and are correlated with hippocampal volumetric cell densities [Sass et al, 1990[Sass et al, , 1992[Sass et al, , 1995. In this series of studies, Sass et al demonstrated in patients with idiopathic left temporal lobe epilepsy statistically significant correlations between presurgical memory impairment (Long Term Retrieval and percent retention on the Wechsler Memory Scale) and hippocampal volumetric cell densities (in CA1, 2, and 3 areas), showing a structural-functional relationship between memory loss and hippocampal volume.…”
Section: Hippocampal-dependent Learning and Memory Hippocampal Volummentioning
confidence: 99%